2015
DOI: 10.1089/chi.2015.0002
|View full text |Cite
|
Sign up to set email alerts
|

Energy Balance 4 Kids with Play: Results from a Two-Year Cluster-Randomized Trial

Abstract: EB4K with Play, which leverages the existing infrastructure of two national programs, increases children's dietary knowledge and may improve weight status and decrease sedentary behaviors among younger children. Future iterations should examine programming specific for different age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Trained peer leader club members offered 2 lunchtime social marketing sessions/week for 5 weeks discussing SNaX messages; film, poster handouts, bookmarks, parent-student activities. N  = 1524 baseline, 2997 posttest a Attrition:7% a Treatment: Delayed treatmentDollahite et al, 2014 [62] N  = 85 baseline; 74 posttestAttrition:13%Treatment: Low-income parents received 8 weekly nutrition education group sessions using the Eating Right is Basic-Enhanced curriculum, facilitated by 8 trained paraprofessionals aiming to increase knowledge, skills, food choices, and goal setting using hands on activities, discussion, and food preparation and tasting. Topics included portion sizes, MyPyramid food groups, food safety, food shopping, menu planning and feeding children. N  = 83 baseline; 60 posttestAttrition:28%Treatment: Delayed treatmentKattelmann et al, 2014 [66] N  = 824 baseline; n  = 618 posttest; n  = 497 followupAttrition: 25% (baseline to posttest); 40% (baseline to follow-up)Treatment: Over a 10-week period, college students had access to 21 mini-web-based lessons to foster healthy weight-related lifestyle behaviors (eating behavior, physical activity, stress management, and non-diet approach to weight management; viewing lessons was not required) and received 3 weekly email nudges (short, entertaining, stage-tailored messages with videos personalized to participant stage of change for F/V consumption, physical activity, and stress management) and 1 nudge reminding them view new lessons, and set goals each week for 1 to 3 targeted behaviors. N  = 815 baseline; n  = 623 posttest, n  = 476 follow-upAttrition: 24% (baseline to posttest); 42% (baseline to follow-up)Treatment: Delayed treatmentMadsen et al, 2015 [100] N  = 583 baselineAttrition: 24% a Treatment: Children in 3rd-5th grade enrolled in low-income school districts were taught for 12-weeks by a registered dietitian using the EB4 K with Play, a multicomponent school-based nutrition and energy balance intervention that included food tastings, physical activity games, strategies to help students meet physical activity and nutrition goals; a registered dietitian worked with school staff and parents to implement wellness policies and improvements in school food service; a play coach offered structured active recess activities before and during school and led a physical activity sessions every other week and 4 afterschool 5-week long sports leagues throughout the year. Teachers were trained to implement Play works games and management strategies in students’ physical education sessions. N  = 296 baselineAttrition: 24% a Treatment: Delayed treatmentHopper et al, 2005 [47] N  = 142Attrition: Not reportedTreatment: For 20-weeks (10 in fall and 10 in spring), trained teachers taught 3rd grade school students 3 30-min physical education group sessions per week that emphasized fitness, tips on walking and biking with parents, and included activities and games and 20 min of aerobic activity in each; 2 30-min nutrition group sessions per week emphasizing nutrition and heart health, reading labels, and tips on how to discuss healthy eating with parents, and included hands-on activities, games, group discussion, and role-playing; and each week a packet of exercise and nutrition activities was sent home for parents and children to use together and then returned the following week.…”
Section: Resultsmentioning
confidence: 99%
“…Trained peer leader club members offered 2 lunchtime social marketing sessions/week for 5 weeks discussing SNaX messages; film, poster handouts, bookmarks, parent-student activities. N  = 1524 baseline, 2997 posttest a Attrition:7% a Treatment: Delayed treatmentDollahite et al, 2014 [62] N  = 85 baseline; 74 posttestAttrition:13%Treatment: Low-income parents received 8 weekly nutrition education group sessions using the Eating Right is Basic-Enhanced curriculum, facilitated by 8 trained paraprofessionals aiming to increase knowledge, skills, food choices, and goal setting using hands on activities, discussion, and food preparation and tasting. Topics included portion sizes, MyPyramid food groups, food safety, food shopping, menu planning and feeding children. N  = 83 baseline; 60 posttestAttrition:28%Treatment: Delayed treatmentKattelmann et al, 2014 [66] N  = 824 baseline; n  = 618 posttest; n  = 497 followupAttrition: 25% (baseline to posttest); 40% (baseline to follow-up)Treatment: Over a 10-week period, college students had access to 21 mini-web-based lessons to foster healthy weight-related lifestyle behaviors (eating behavior, physical activity, stress management, and non-diet approach to weight management; viewing lessons was not required) and received 3 weekly email nudges (short, entertaining, stage-tailored messages with videos personalized to participant stage of change for F/V consumption, physical activity, and stress management) and 1 nudge reminding them view new lessons, and set goals each week for 1 to 3 targeted behaviors. N  = 815 baseline; n  = 623 posttest, n  = 476 follow-upAttrition: 24% (baseline to posttest); 42% (baseline to follow-up)Treatment: Delayed treatmentMadsen et al, 2015 [100] N  = 583 baselineAttrition: 24% a Treatment: Children in 3rd-5th grade enrolled in low-income school districts were taught for 12-weeks by a registered dietitian using the EB4 K with Play, a multicomponent school-based nutrition and energy balance intervention that included food tastings, physical activity games, strategies to help students meet physical activity and nutrition goals; a registered dietitian worked with school staff and parents to implement wellness policies and improvements in school food service; a play coach offered structured active recess activities before and during school and led a physical activity sessions every other week and 4 afterschool 5-week long sports leagues throughout the year. Teachers were trained to implement Play works games and management strategies in students’ physical education sessions. N  = 296 baselineAttrition: 24% a Treatment: Delayed treatmentHopper et al, 2005 [47] N  = 142Attrition: Not reportedTreatment: For 20-weeks (10 in fall and 10 in spring), trained teachers taught 3rd grade school students 3 30-min physical education group sessions per week that emphasized fitness, tips on walking and biking with parents, and included activities and games and 20 min of aerobic activity in each; 2 30-min nutrition group sessions per week emphasizing nutrition and heart health, reading labels, and tips on how to discuss healthy eating with parents, and included hands-on activities, games, group discussion, and role-playing; and each week a packet of exercise and nutrition activities was sent home for parents and children to use together and then returned the following week.…”
Section: Resultsmentioning
confidence: 99%
“…A quasi-experimental design Besides, evaluation details are provided in the Supplementary Material. According to the evaluation results, 10 of the studies were evaluated as strong [40,47,49,50,52,[54][55][56][57][58] and the remaining nine studies were evaluated as moderate. There were no studies evaluated as weak.…”
Section: Shore Et Al [54]mentioning
confidence: 99%
“…The studies revealed the main outcomes, including: BMI (kg/m 2 ), waist circumference, skinfold and body fat percentage related to obesity parameters [40][41][42][43][45][46][47][49][50][51][52][53]56], the level of PA [45,[48][49][50][51][52]54,55,57,58] and various variables related to PF components [42,49,[52][53][54]56] during school years. Measurements of MVPA recommended in these studies were interpreted by measuring with the survey method in some studies [40,50,57] and by way of pedometer or accelerometer in some others [44,45,[47][48][49]51,52,54,55,58]. In the studies where BMI (kg/m 2 ) measurements were reported, it was found that body mass index was measured by taking height and weight measurements with standard tools.…”
Section: Main Outcomes Regarding Obesity Parameters Physical Activitmentioning
confidence: 99%
See 2 more Smart Citations